2020
DOI: 10.1111/eci.13362
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adverse prognosis in COVID‐19: A systematic review and meta‐analysis

Abstract: Background: Identification of reliable outcome predictors in coronavirus disease 2019 (COVID-19) is of paramount importance for improving patient's management. Methods: A systematic review of literature was conducted until 24 April 2020. From 6843 articles, 49 studies were selected for a pooled assessment; cumulative statistics for age and sex were retrieved in 587 790 and 602 234 cases. Two endpoints were defined: (a) a composite outcome including death, severe presentation, hospitalization in the intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
275
2
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(315 citation statements)
references
References 53 publications
20
275
2
18
Order By: Relevance
“…Chronic renal disease was not associated with ICU admission, though it was the comorbidity with the highest risk of death and its association with mortality has been highlighted elsewhere [45]. Cardiovascular disease was a consistent risk factor across all severe outcomes [46], even though it was not the strongest one.…”
Section: Discussionmentioning
confidence: 91%
“…Chronic renal disease was not associated with ICU admission, though it was the comorbidity with the highest risk of death and its association with mortality has been highlighted elsewhere [45]. Cardiovascular disease was a consistent risk factor across all severe outcomes [46], even though it was not the strongest one.…”
Section: Discussionmentioning
confidence: 91%
“…The breadth of SARS-CoV-2 infection severity ranges from no symptoms to critical illness that can result in pneumonia and respiratory failure [ 2 ]. Several risk factors for severe COVID-19 disease have been identified, including age (≥50 years old), male sex, and comorbidities such as hypertension, diabetes mellitus, and cardiovascular disease [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy enhances the risk of thromboembolic complications due to the increased levels of coagulation factors in the blood [ 20 ]. Increased D-dimer concentration in COVID-19 patients, indicating degradation of a blood clot, correlates with poorer outcomes [ 3 ]. COVID-19 may further enhance hypercoagulability in pregnant individuals, putting them at even greater risk for thromboembolism [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies in Qatar and Kuwait, specifically focusing on ICU admission, stressed the increased risk associated with DM [24], in contrast with our results, findings in the literature are quite heterogeneous. Actually, meta-analyses found that DM was associated with higher risk of composite event combining ICU admission with mortality and/or severe/critical form of the disease [25,26,27], while other meta-analyses found an absence of increased ICU risk [28,29] or the evidence inconclusive [30]. Furthermore, to our knowledge, most studies did not account for the time component in their analysis and none used a flexible model.…”
Section: Results Derived From the Modelsmentioning
confidence: 98%